MEMBACA POLITIK KEBANGSAAN NU DAN MUHAMMADIYAH - Alhini Zahratana; Muhammad Izul Ridho (Mozaic: Islamic Studies Journal, 2023)
General elections are a means of democracy for citizens and are citizens' rights guaranteed by the constitution in the 1945 Constitution. Therefore, elections must be carried out democratically by referring to international standards which contain 15 points. In this case, elections are the most appropriate mechanism chosen to make it happen. Recently, many people have highlighted the discourse of postponing the 2024 election. The reason for this discourse is because the community's economy has not recovered due to the Covid-19 pandemic and the government wants to focus on economic recovery first rather than political affairs (elections). Apart from these reasons, the public is considered satisfied with Jokowi's performance. The series of events that occurred after the declaration of the proposed postponement of the election drew many comments. Among those who responded were Muhammadiyah and NU. The first group said that the postponement could be done but from an ethical perspective, according to him, it would be very problematic. This is similar to the opinion of most NU. The opinions of these two large organizations are based on khittah which are not much different from each other.